Estimating the effect of incident delirium on short‐term outcomes in aged hip fracture patients through propensity score analysis. Issue 7 (26th September 2014) - Radinovic, Kristina; Markovic‐Denic, Ljiljana; Dubljanin‐Raspopovic, Emilija; Marinkovic, Jelena; Milan, Zoka; Bumbasirevic, Vesna
<x xml:space="preserve">Abstract</x> Aim We aimed to evaluate the factors contributing to delirium after hip fracture and assess the effect of incident delirium on short‐term clinical outcomes. Methods A total of 270 non‐delirious, consecutive hip fracture patients 60 years and older were included in a prospective cohort study. The patients were assessed with respect to physical status according to the American Society of Anesthesiologists classification, medical comorbidities with the Charlson Comorbidity Index, cognitive function with the Portable Mental Status Questionnaire and depression with the Geriatric Depressive Scale. Incident delirium was evaluated daily. Clinical outcomes and 1‐month mortality were recorded. Results Incident delirium was present in 53.0% of patients. Patients with delirium were older (P = 0.046), had higher American Society of Anesthesiologists and Charlson Comorbidity Index scores (P < 0.001), lower Portable Mental Status Questionnaire scores and higher Geriatric Depressive Scale scores (P < 0.001, P = 0.003, respectively). After adjusting for age, multivariate regression analysis in the first model showed that patients with delirium were at higher risk of reintervention plus death (P < 0.05), complications P < 0.001), a higher severity complication score (P < 0.05) and longer length of hospital stay (P < 0.001). In the second model, after adjusting for propensity score, patients with delirium were at higher risk of reintervention plus death (P < 0.05) and longer length of hospital stay (P < 0.01). Conclusions Patients who are older, with worse physical status, worse cognitive function and depression are more likely to develop delirium after hip fracture. Incident delirium has negative independent effects on short‐term outcomes in elderly patients after hip fracture. Geriatr Gerontol Int 2015; 15: 848–855.